Theoretical evaluation of wall teichoic acids in the cavitation-mediated pores formation in Gram-positive bacteria subjected to an electric field - Rauch, Cyril; Leigh, James A. (Elsevier, 2014)
Background: Electroporation is a method of choice to transform living cells. The ability of electroporation to transfer small or large chemicals across the lipid bilayer membrane of eukaryotic cells or Gram-negative bacteria relies on the formation of transient pores across the membrane. To exist, these pores rely on an insulator (the bilayer membrane) and the presence of a potential difference on either side of the membrane mediated by an external electric field. In Gram-positive bacteria, however, the wall is not an insulator but pores can still form when an electric field is applied. Past works have shown that the electrostatic charge of teichoic acids, a major wall component; sensitizes the wall to pore formation when an external electric field is applied. These results suggest that teichoic acids mediate the formation of defects in the wall of Gram-positive bacteria. Methods: We model the electrostatic repulsion between teichoic acids embedded in the bacterial wall composed of peptidoglycan when an electric field is applied. The repulsion between teichoic acids gives rise to a stress pressure that is able to rupture the wall when a threshold value has been reached. The size of such small defects can diverge leading to the formation of pores. Results: It is demonstrated herein that for a bonding energy of about ~ 1 − 10 kBT between peptidoglycan monomers an intra-wall pressure of about ~ 5 − 120 kBT/nm3 generates spherical defects of radius ~ 0.1 − 1 nm diverging in size to create pores. Conclusion: The electrostatic cavitation of the bacterial wall theory has the potential to highlight the role of teichoic acids in the formation pores, providing a new step in the understanding of electroporation in Gram positive bacteria without requiring the use of an insulator.